2012
DOI: 10.3391/ai.2012.7.2.009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in native and introduced populations of the red swamp crayfish Procambarus clarkii (Girard, 1852) (Crustacea, Decapoda, Cambaridae) in Mexico and Costa Rica

Abstract: The invasive ctenophore, Mnemiopsis leidyi, which had its first mass occurrence in Limfjorden (Denmark) . During that period, copepods and other mesozooplankton organisms were virtually absent while ciliates were a substantial part of the zooplankton biomass. In "pre-Mnemiopsis years", there seems to have been large variability in the grazing impact on zooplankton depending on the seasonal abundance of A. aurita. With the addition of the second carnivore M. leidyi, however, additional predation pressure caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 24 publications
2
21
0
3
Order By: Relevance
“…The invasive signal crayfish populations we studied had small effective population sizes and low to moderate genetic diversity, despite having been established for more than 25 years ( c . 25 generations), which is similar to what is observed in other invasive crayfish species populations, (e.g., the red swamp crayfish ( Procambarus clarkii ) in China (Yue, Li, Bai, Wang, & Feng, ), Mexico and Costa Rica (Belfiore & May, ; NBN ; Torres & Álvarez, ). It is possible that the low levels of heterozygosity observed are the result of recurrent translocations of small numbers of signal crayfish which may have resulted in founder effects (Gouin, Grandjean, & Souty‐Grosset, ).…”
Section: Discussionsupporting
confidence: 81%
“…The invasive signal crayfish populations we studied had small effective population sizes and low to moderate genetic diversity, despite having been established for more than 25 years ( c . 25 generations), which is similar to what is observed in other invasive crayfish species populations, (e.g., the red swamp crayfish ( Procambarus clarkii ) in China (Yue, Li, Bai, Wang, & Feng, ), Mexico and Costa Rica (Belfiore & May, ; NBN ; Torres & Álvarez, ). It is possible that the low levels of heterozygosity observed are the result of recurrent translocations of small numbers of signal crayfish which may have resulted in founder effects (Gouin, Grandjean, & Souty‐Grosset, ).…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, the studies that found low genetic diversity (Torres and Álvarez, 2012) argue that despite this fact, populations are still successful in establish and flourish due to a phenomenon named "general-purpose genotype" proposed by Baker (1965), in which different phenotypes would be produce through plasticity and thus, the population would be able to cope with different environmental conditions. High genetic diversity in invasive populations is usually related to multiple introductions or the existence of gene flow among established populations while low genetic diversity is associated with isolated introductions, founder effect and genetic bottlenecks.…”
Section: Geneticsmentioning
confidence: 99%
“…One of these, Procambarus clarkii (Girard, 1852) occurs naturally in North America (north‐eastern Mexico and in south‐central USA) (Hobbs, ). In South America, this species has been recorded in Ecuador and Brazil (Magalhães et al ., ; Torres and Álvarez, ) and information generated using the Species Distribution Models (SDMs) reveals other areas suitable for species occupation, especially in southern South America (Paraguay, Chile, Argentina, Uruguay and Brazil) (Palaoro et al ., ). Other non‐native species have been introduced from Oceania (Lawrence and Jones, ): Cherax quadricarinatus (von Martens, 1868), Cherax tenuimanus Smith, 1912 and Cherax cainii Austin, 2002 (Austin and Bunn, ; Mendoza et al ., ).…”
Section: State Of Knowledgementioning
confidence: 97%